2021
DOI: 10.2528/pierc21052404
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sparse Planar Array Synthesis Model for Microwave Power Transmission Systems With High Efficiency and Low Cost

Abstract: A novel algorithm is developed to realize the optimal synthesis of a sparse nonuniformamplitude nonuniform-distribution planar array (SNANDPA) in microwave power transmission (MPT) systems. The dual compression factor particle swarm optimization (DCFPSO) algorithm and the subarray partition technique are adopted to realize the optimal synthesis of SNANDPA. The DCFPSO algorithm first optimizes beam collection efficiency (BCE ) and side-lobe level outside the receiving region (CSL) of SNANDPA which ensure effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The second planar array model is a Nonuniform Distributed Rectangular Planar Array (NDRPA), such an overall model has higher optimization freedom and may get better results. If readers want to know the physical model of NDRPA, you can refer to the model of SNANDPA in [9]. The third array model optimizes only the globally optimal individuals (only-gbest) in SQSRA.…”
Section: Simulations and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second planar array model is a Nonuniform Distributed Rectangular Planar Array (NDRPA), such an overall model has higher optimization freedom and may get better results. If readers want to know the physical model of NDRPA, you can refer to the model of SNANDPA in [9]. The third array model optimizes only the globally optimal individuals (only-gbest) in SQSRA.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…[9] Ref. [13] According to Table 4, it can be concluded that the BCE achieved by the proposed method is 1.95% higher than the result in [9] (BCE| N DRP A = 93.04% vs. BCE| [9] = 91.09%). Although the array in [13] is a fully populated and uniformly excited array (γ a =1), the BCE only reaches 91%.…”
Section: Comparison With Other Planar Arrays In Bcementioning
confidence: 89%
See 3 more Smart Citations